The Red Sea Scrolls - Allen, Woody (The Biblical archaeology review, 1975)
Scholars will recall that several years ago a shepherd, wandering in the Gulf of Aquaba, stumbled upon a cave containing several large clay jars and also two tickets to the ice show. Inside the jars were discovered six parchment scrolls with ancient incomprehensible writing which the shepherd, in his ignorance, sold to the museum for $750,000 apiece. Two years later the jars turned up in a pawnshop in Philadelphia. One year later the shepherd turned up in a pawnshop in Philadelphia and neither was claimed.